2015
DOI: 10.4236/gep.2015.38003
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Suitability Modeling of Endangered Primates in Nigeria: Integrating Satellite Remote Sensing and Spatial Modeling Techniques

Abstract: This paper investigates the impacts of forest cover and spatial structure changes on the forest landscape across Afi-Mbe-Okwangwo protected area of Cross River State, Nigeria and its corresponding implication on two endangered primates (Cross River Gorilla and Nigeria-Cameroon Chimpanzee) habitat using satellite remote sensing and modeling techniques. Using remote sensing change detection analysis, the spatial extent and annual rate of deforestation for the study area was determined as 34,620 hectares and 1.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
(38 reference statements)
0
10
0
2
Order By: Relevance
“…Nhờ khả năng thu thập thông tin trên phạm vi khu vực và toàn cầu, viễn thám với các cảm biến quang học và cảm biến Radar (SAR) là hai trong số những loại dữ liệu viễn thám được sử dụng để ước tính định lượng sinh khối và giám sát diện tích ruộng lúa [5], [6]. Các nghiên cứu trước đây thường sử dụng cảm biến quang học với độ phân giải không gian thấp (Modis), trung bình (Landsat) và cao (Sentinel-2) để giám sát và ước tính năng suất lúa [7]- [9].…”
Section: Tính Cấp Thiếtunclassified
See 1 more Smart Citation
“…Nhờ khả năng thu thập thông tin trên phạm vi khu vực và toàn cầu, viễn thám với các cảm biến quang học và cảm biến Radar (SAR) là hai trong số những loại dữ liệu viễn thám được sử dụng để ước tính định lượng sinh khối và giám sát diện tích ruộng lúa [5], [6]. Các nghiên cứu trước đây thường sử dụng cảm biến quang học với độ phân giải không gian thấp (Modis), trung bình (Landsat) và cao (Sentinel-2) để giám sát và ước tính năng suất lúa [7]- [9].…”
Section: Tính Cấp Thiếtunclassified
“…Trong những năm gần đây, các thuật toán học máy khác nhau đã được phát triển nhanh (mạng nơ-ron nhân tạo -ANN, máy vectơ hỗ trợ -SVM, rừng ngẫu nhiên -RF, cây quyết định -DT), đã được phát triển để lập bản đồ ruộng lúa và các loại cây trồng khác [5], [6]. Khả năng tổng quát hóa và chống nhiễu của các phương pháp học máy đã được chứng minh trong trường hợp dữ liệu mẫu ít, thuật toán học máy đã trở thành phương pháp hữu ích để xử lý dữ liệu viễn thám lớn và cung cấp các giải pháp trong lĩnh vực nông nghiệp.…”
Section: Tính Cấp Thiếtunclassified
“…To build the model, the authors referred to the protocols suggested by various studies (Bradie & Leung,2017;Halvorsen 2013;Kaky et al,2020;Zhang et al, 2019), and selected several basic environmental factors, including terrain, vegetation, human disturbance variables, and climate data (Table 1), which are widely available for many locations around the world. MaxENT was adopted to develop the models (Elith et al, 2011;Phillips & Dudík, 2008), as it is a widely applied method to predict species distributions and proven to be reliable for numerous taxa (Kumar & Stohlgren, 2009;Onojeghuo et al, 2015;Khadka et al, 2017;Thapa et al, 2018). Before running MaxENT, all relevant accessible factors in the dataset were given full consideration and transformed into raster format (90m × 90m), using UTM coordination system.…”
Section: Data Sourcementioning
confidence: 99%
“…For the purposes of our study, we treated the two divisions of the CRNP as separate PAs. Afi (c. 100 km 2 ) and Mbe (c. 85 km 2 ) lie to the west of the Okwangwo Division of CRNP and are important sites for endemic and threatened species, including drill (Mandrillus leucophaeus), Cross River gorilla (Gorilla gorilla diehli), Nigeria-Cameroon chimpanzee (Pan troglodytes ellioti) and grey-necked rockfowl (Picathartes oreas; Morgan et al 2011, Bergl et al 2012, Atuo et al 2014, Dunn et al 2014, Onojeghuo et al 2015, Agaldo et al 2016. Villages around these PAs generally consist of small homesteads that rely substantially on forest resources for their daily substance.…”
Section: Environmental Conservationmentioning
confidence: 99%
“…However, these services are threatened by deforestation originating from illegal logging and conversion of forestlands to farmlands (Bergl et al 2012). This has resulted in c. 1.5% (34 620 ha) loss of the forest cover between 2000 and 2014 alone and a projection of 16% loss by 2028 if the current rate of loss is not checked (Onojeghuo et al 2015).…”
Section: Environmental Conservationmentioning
confidence: 99%